2005
DOI: 10.1080/10673220590923164
|View full text |Cite
|
Sign up to set email alerts
|

Toward Convergence in the Medication Treatment of Bipolar Disorder and Schizophrenia

Abstract: Reaching a correct differential diagnosis among patients with psychotic symptoms was especially important during the era of first-generation antipsychotics, when treatments for the different disorders varied in terms of adverse events and likelihood of response. The historical "overdiagnosis" of schizophrenia and "underdiagnosis" of bipolar disorder in the United States was blamed for an increased exposure to neuroleptics among patients who might have benefited from lithium. With the recognition that second-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 104 publications
(99 reference statements)
0
17
0
Order By: Relevance
“…Common molecular causes have been proposed for affective disorders and schizophrenia (Citrome et al 2005; Craddock et al 2006; Van Den Bogaert et al 2006). Our data suggests bipolar disorder and major depressive disorder are associated with abnormal muscarinic receptor expression, as has been reported in schizophrenia (Dean et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Common molecular causes have been proposed for affective disorders and schizophrenia (Citrome et al 2005; Craddock et al 2006; Van Den Bogaert et al 2006). Our data suggests bipolar disorder and major depressive disorder are associated with abnormal muscarinic receptor expression, as has been reported in schizophrenia (Dean et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the co-administration of second generation antipsychotics with mood stabilizers for BD, mood stabilizers such as lithium or anticonvulsants have been used together with antipsychotics as adjunctive medication for the treatment of schizophrenia, for the same purpose of producing potential synergistic or enhanced responses (Citrome et al, 2005; Johannessen, 2008). Although adjunctive lithium treatment in early studies seemed to be somewhat beneficial (Carman et al, 1981; Kellams et al, 1976; Small et al, 1975), later, well-designed trials found that this treatment strategy did not produce robust evidence of improvement.…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 99%
“…Second-generation antipsychotics have emerged as “mood stabilizers”, rivaling classic agents such as lithium and certain anticonvulsants such as valproate and carbamazepine (Citrome et al 2005a). The second-generation antipsychotics, as monotherapies, can successfully treat bipolar mania, even in the absence of psychotic symptoms, as demonstrated by many clinical trials.…”
Section: Is Aripiprazole Worth Using?mentioning
confidence: 99%